Reviewing Indonesian Wooden Furniture: Does Indonesia Have Comparative and Competitive Advantages in the United States Market? - Made Nurani Wikantari; Ketut Budi Susrusa; Gede Mekse Korri Arisena; Suryani Nurfadillah; Kadhung Prayoga (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
The Indonesian wood furniture industry is a significant contributor to the non-oil and gas sector of the economy. Manufacturers are responsible for meeting not only domestic demands but also the needs of the international market. Nevertheless, Indonesia's status as a global exporter remains comparatively inferior to that of China and Vietnam. This study aimed to assess the comparative and competitive advantages of Indonesian wooden furniture globally. Employing a time series analysis spanning 21 years (2001-2022), the research utilized the Revealed Comparative Advantage (RCA) method and Porter’s Diamond Model to assess these advantages. The results of the study indicate that RCA analysis consistenly showed values greater than one. However, the study also identified fluctuations in RCA during the period of 2007-2011. Furthermore, the application of Porter’s Diamond Model revealed that Indonesia’s abundant natural resources, skilled labor force, and supportive industrial ecosystem are key factors contributing to its competitive position. Nevertheless, the analysis highlighted the need for continued investment in capital, particularly in terms of technology and infrastructure, to sustain and echance this competitive advantage.